Cognitive, emotional and social learning in the audiovisual area. Successful cases during the pandemic - Saavedra Llamas, Marta (2023)
The COVID-19 health crisis posed a new scenario for society, having a ripple effect in, academic areas; to a greater extent, the audiovisual. University entities were ahead of events and proposed TRIC practices that would serve for the times that were to come and that in many cases were ahead of now normalized actions. This research analyzes the cognitive, emotional and social learning acquired by students in quarantine and how the realization of Radio Nebrija in the radio field and Nebrija Talent in the television field, two TRIC projects based on an ABP methodology, served to configure new working models for students and new university dynamics for teachers. The change from ICT context to TRIC is exposed and through a discussion group with young students and in-depth interviews with experts in the field of teaching and learning environments. The effedtiveness od intermethodology in academic environments emerges from the research.